EXPLORING THE VIEWS OF MUSLIM IN DEPICTING PEOPLE IN SOCIAL MEDIA - Ulfya Syahara Razaq, Siti (UIN Sunan Gunung Djati Bandung, 2024)
This paper explores social media conversations by Muslims through discourse analysis. The study looks into TikTok App about the view of Islam and Muslims in representation of other on social media. A discourse analysis of Tiktok App reveals that people are changing their perceptions, attitudes and opinions through the TikTok App. Netizens like, comment and share the material in accordance with their interests and ideology. The previous study has found that Islam is the only religion on social media which is being portrayed in a negative fashion. The hot discourses that found are jihad, niqab, hijab, mosques, terrorism, which were the most common discourses on Facebook. On the other hand, this study will take from the Muslims perspective on the issues social media. Follow the following pattern: General statement about the importance of the topic, gap in literature or discrepancies between theories and practices, purpose of study, method, main findings, and conclusion.